Environmental participation and environmental motivation - Benno Torgler; María A. García Vali\~nas; Alison Macintyre (Fondazione Eni Enrico Mattei (FEEM), 2008)
We explore whether environmental motivation affects environmental behavior by focusing on volunteering. The paper first introduces a theoretical model of volunteering in environmental organizations. In a next step, it tests the hypothesis working with a large micro data set covering 32 countries from both Western and Eastern Europe using several different proxies to measure environmental motivation. Our results indicate that environmental motivation has a strong impact on individuals' voluntary engagement in environmental organizations. A higher level of environmental motivation due to higher environmental moral standards may lead to a stronger voluntary involvement in environmental organizations.
Keywords: D11; H41; H26; H73; D64; 330; Environmental Participation; Environmental Motivation; Environmental Morale; Pro-environmental Attitudes; Social Capital